Graphdiyne multilayer composite film and preparation method thereof

By growing graphyne transition layer and organic polymer layer in situ on the porous base film, the graphyne multi-layer composite film is formed, which solves the problems of nanomaterial agglomeration and polymer pore penetration, and improves the efficiency and membrane performance of bioethanol recovery , broaden the application of graphite alkyne materials.

CN119318887AActive Publication Date: 2025-01-17BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411613757.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-17
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing permeable alcohol permeable vaporized membranes have problems with nanomaterial agglomeration and polymer pore penetration in bioethanol recovery, resulting in a degradation of performance. The lack of high-performance membrane materials limits the efficiency of bioethanol recovery.

Method used

The design of graphyyne multi-layer composite film is adopted. By growing graphyyne transition layer and organic polymer layer in situ on the porous base film, a top-down three-layer structure is formed to avoid agglomeration and pore seepage, and the adsorption of alcohols is enhanced. performance.

Benefits of technology

Improve the separation performance and stability of the membrane, increase the recovery efficiency of alcohols, and increase the separation factor by 30%-50% compared with traditional membranes, and increase the permeability flux and separation factor by 30%-90%, widening graphite alkyne materials application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005131595410000011
    Figure HDA0005131595410000011
  • Figure HDA0005131595410000012
    Figure HDA0005131595410000012
  • Figure HDA0005131595410000021
    Figure HDA0005131595410000021
Patent Text Reader

Abstract

The invention discloses a graphdiyne multilayer composite membrane and a preparation method thereof, and belongs to the technical field of membrane separation. A porous base membrane with an alkynyl layer is obtained by adopting a two-step modification method, then the porous base membrane is soaked in a solution containing a graphdiyne monomer and a catalyst, and a reaction is performed at a certain temperature, so that a graphdiyne material fully grows on the surface of the porous base membrane. Adding a membrane casting solution formed by mixing an organic polymer, a cross-linking agent, a catalyst and an organic solvent to the surface of the graphdiyne-loaded porous base membrane, volatilizing the organic solvent, and curing at 80 DEG C to form the membrane. The ethanol permselective membrane has a three-layer membrane structure, namely the organic polymer layer, the ultrathin graphdiyne transition layer and the porous support layer, so that the problems of agglomeration and pore permeation of a nano material are effectively avoided, and the adsorption process of ethanol is further enhanced. The membrane prepared by the invention has higher pervaporation alcohol permeation performance, can efficiently and stably recover alcohols, and provides reference for the development of a novel pervaporation membrane structure with preferential alcohol permeation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane separation and technology, and specifically relates to a graphyne multilayer composite membrane and a preparation method thereof. Background Art

[0002] In recent years, bioethanol recovered from biofermentation has attracted widespread attention due to its clean and recyclable characteristics, which can alleviate the shortage of fossil energy and further environmental degradation. However, low product concentrations in fermentation broth often lead to high energy consumption in the bioethanol recovery process. Pervaporation (PV) is considered as an alternative technology for bioethanol recovery. However, due to the continued lack of strong and high-performance membrane materials, the progress of pervaporation membranes for preferential alcohol permeation has lagged behind.

[0003] Polydimethylsiloxane (PDMS) is one of the most widely used membrane materials for alcohol-preferential pervaporation membranes, but its separation performance is often limited by the "trade-off" phenomenon between permeability and selectivity. To address this challenge, composite membranes and mixed matrix membranes (MMMs) have been proposed to improve permeation selectivity by adding porous fillers to polymers to adjust the stacking of polymer chains and provide more adsorption sites for permeable molecules. So far, various nanomaterials such as metal organic scaffolds (MOFs), covalent organic scaffolds (COFs), zeolites, and carbon nanotubes (CNTs) have been used for filling.

[0004] However, most preparation methods for loading porous fillers on the membrane surface are to blend with polymers, which usually leads to nanoparticle agglomeration, polymer pore permeation and other phenomena, which seriously affect the performance of mixed matrix membranes. In the preparation process of pervaporation membranes, reducing agglomeration and pore permeation is one of the most effective ways to improve membrane separation performance. Therefore, designing a membrane that can avoid both particle agglomeration and polymer pore permeation is of great significance for selective ethanol recovery.

[0005] At the same time, graphyne is composed of sp and sp 2 A new two-dimensional carbon allotrope formed by covalently linked hybrid carbon atoms. It has the characteristics of ordered structure, hexagonal pores and excellent thermochemical stability. Its inherent porous system can provide a relatively short transport pathway for molecules, which is conducive to enhancing the permeation flux.

[0006] Based on the above analysis, the present invention in situ grows two-dimensional gyne nanomaterials on a substrate to form an ultra-thin gyne transition layer, and impregnates an organic polymer to prepare a composite membrane with a unique transition layer structure. The transition layer effectively avoids the agglomeration of nanomaterials and the pore permeation of polymers, and further enhances the adsorption process of ethanol. The recovery of alcohols is achieved through the pervaporation process, further enriching the types of membrane structures that preferentially permeate alcohols, and broadening the application field of gyne materials, accelerating the pace of their industrial application. Summary of the invention

[0007] The key technical problem to be solved by the present invention is to provide a method for preparing a Graphene Oxide Multilayer Composite Membrane, thereby avoiding the problems of polymer pore permeation and nanomaterial agglomeration, and enhancing the adsorption of alcohols, thereby further improving the performance of the alcohol preferential permeation membrane in the recovery of alcohols. The specific technical solution is as follows:

[0008] A graphyne multilayer composite membrane, characterized in that it is divided into three layers, from top to bottom: an organic polymer layer, a graphyne transition layer, and a lower porous base membrane support layer; the graphyne transition layer is on the upper surface of the porous base membrane and grows upward from the upper surface of the porous base membrane; the organic polymer layer is loaded on the surface of the graphyne transition layer; the graphyne transition layer and the organic polymer layer together constitute a selective separation layer.

[0009] The thickness of the graphyne transition layer is 100-400 nm, and the thickness of the organic polymer layer is 1-5 μm. Preferably, the thickness of the selective separation layer composed of the graphyne transition layer and the organic polymer layer is 1.1-5.4 μm.

[0010] The Graphene transition layer is grown using 1,3,5-triethynylbenzene as the Graphene monomer, which is a nanomaterial with extremely strong hydrophobicity.

[0011] Preferably, the porous base membrane is selected from an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane, and has an average pore size of 0.01-100 μm.

[0012] Specifically, the porous base membrane may be in the form of a flat plate, a tube or a hollow fiber.

[0013] The method for preparing a Graphene multilayer composite film of the present invention comprises the following steps:

[0014] Step a, chemically modifying the surface of the porous base film with an amino-terminated silane coupling agent to make the surface of the base film have amino active groups, and then grafting small molecules with alkynyl groups that can react with amino groups to obtain a functional porous base film with an alkynyl-based layer;

[0015] Step b, dissolving a certain amount of graphyne monomer in a solvent, adding copper acetate powder, stirring and ultrasonically treating, to prepare a mixed solution of graphyne monomer and copper acetate; immersing the functionalized porous base film on which the acetylene base layer is grown in step a in the mixed solution, and reacting at a certain temperature, so that the graphyne transition layer is fully grown on the surface of the porous base film;

[0016] Step c, taking an organic polymer, a cross-linking agent, and a catalyst and mixing them evenly to form a cross-linking solution, then mixing the cross-linking solution and an organic solvent evenly to form a casting liquid 1, adding a certain amount of the casting liquid 1 to the surface of the porous base film on which the graphyne transition layer is grown in step b, leaving a portion of the casting liquid 1 on the surface of the graphyne transition layer to form a corresponding organic polymer layer; then after the organic solvent is volatilized for 3-12 hours, the membrane is placed in an environment of 80°C to react for 8 hours to obtain a graphyne multilayer composite membrane.

[0017] Specifically, the use of an amino-terminated silane coupling agent to chemically modify the surface of the porous base membrane in step a is preferably carried out by: immersing the porous base membrane in an ethanol solution of an amino-terminated silane coupling agent with a concentration of 0.1-1 mM, reacting at 100-150° C. for 1-3 hours after nitrogen protection; the amino-terminated silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethoxydimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethoxydiethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane, aminoethylaminoethylaminopropyltrimethoxysilane, and polyaminoalkyltrialkylsilane.

[0018] Specifically, the grafted alkynyl small molecule that reacts with the amino group in step a is selected from one or more of 4-ethynylbenzaldehyde, 3-ethynylbenzaldehyde, 2-ethynylbenzaldehyde, 5-ethynylisophthalic acid, 4-ethynylbenzoic acid, 3,5-diethynylbenzoic acid, 3-ethynylbenzoic acid, 2-ethynylbenzoic acid, 3-ethynyl-4-methylbenzoic acid, and 2-chloro-4-ethynylbenzoic acid. The porous base film after surface amination is immersed in an ethanol solution of the alkynyl small molecule that reacts with the amino group at a concentration of 0.5-5 mg / ml, and reacted at 100-150° C. for 1-3 hours.

[0019] Step b, specifically, the Graphene monomer is 1,3,5-triethynylbenzene. The concentration of the Graphene monomer is 0.4-5 mg / ml; the solvent used is selected from one of methanol, ethanol, and n-propanol. The concentration of copper acetate is 0.2-1 g / L, preferably 0.5 g / L. Reaction at a certain temperature refers to reaction at 100°C-150°C for 2-6 hours.

[0020] Specifically, the organic polymers described in step c are one or more of polydimethylsiloxane (PDMS), polyether block polyamide (PEBA), polyphenylmethylsiloxane (PPMS), polytrifluoropropylmethylsiloxane (PTFMS) or polytrimethylsilyl propyne (PTMSP); the crosslinking agent is one or more of tetraethyl orthosilicate (TEOS), propoxypropyl orthosilicate (TPOS), vinyl triethoxysilane (VTES), ethyl triethoxysilane (ETES) or trifluoropropyl triethoxysilane (TFPTES); the catalyst is one or more of dibutyltin dilaurate (DBTDL), monobutyltin oxide (MBTO), dibutyltin oxide (DBTO), tripropyltin oxide (TPTO) or chloroplatinic acid.

[0021] Specifically, the method for loading the organic polymer in step c is one or more of vacuum filtration, titration coating, spray coating, and dip coating.

[0022] Preferably, the content of the organic polymer in the casting solution 1 in step c is 5wt.%-50wt.%.

[0023] Preferably, the organic solvent in step c is one or more of ethanol, n-heptane, n-hexane or cyclohexane; the content of the crosslinking agent in the crosslinking solution is 1wt.%-30wt.%, and the content of the catalyst is 0.1wt.%-5wt.%.

[0024] The application of the Graphene multilayer composite membrane of the present invention separates bio-alcohol from aqueous solution or fermentation liquid in the form of pervaporation.

[0025] The technical solution provided by the present invention has the following beneficial effects: the present invention has a three-layer membrane structure of an organic polymer layer, a gypsum transition layer and a porous support layer from top to bottom. The outermost organic polymer layer effectively improves the separation performance through dense polymer; the in-situ grown gypsum transition layer of the middle layer can effectively increase the binding force between the support layer and the inorganic nanomaterial, while effectively avoiding problems such as agglomeration and pore permeation that affect the membrane performance; the innermost porous support layer provides support for the selective separation layer of the membrane, thereby increasing the stability of the membrane. The prepared gypsum multilayer composite membrane can efficiently and stably recover alcohols. In addition, compared with the traditional pure polymer membrane, the separation factor of the membrane is increased by 30%-50% under the condition of the same membrane thickness. Compared with the casting liquid made by blending nanomaterials with polymers, the in-situ growth method makes it possible to increase the permeation flux and separation factor of the membrane by 30%-50% and 60%-90% respectively compared with the traditional mixed matrix membrane when the amount of graphyne monomer is the same. The in-situ growth of graphyne as an ultra-thin transition layer further improves the separation performance of the graphyne multilayer composite membrane, provides inspiration for the development of new structure preferential alcohol permeation membranes, and further broadens the application field of graphyne. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 .The graphyne multilayer composite film prepared in Example 1 of the present invention includes (1-1) water contact angle test graph, (1-2) surface and (1-3) cross-section scanning electron microscope images, (1-4) cross-section energy dispersion X-ray spectrum of Si and Al elements, and (1-5) water contact angle test graph and (1-6) surface scanning electron microscope image of the graphyne transition layer.

[0027] Figure 2 .Scanning electron microscope images of the pure PDMS membrane (2-1) water contact angle test image, (2-2) surface and (2-3) cross section of the prepared comparative example 1 of the present invention.

[0028] Figure 3 .Scanning electron microscope images of the (3-1) water contact angle test image, (3-2) surface and (3-3) cross section of the Graphene mixed matrix membrane prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the embodiments of the present invention will be further described in detail below in conjunction with the accompanying drawings, but the present invention is not limited to the following examples. The scanning electron microscope surface image and cross-sectional image are observed and measured using a TESCAN MIAI3 scanning electron microscope (SEM). The water contact angle is observed and measured using an SDC-300 contact angle goniometer.

[0030] The embodiment of the present invention provides a graphyne multilayer composite mold and a preparation method thereof, characterized in that it comprises a three-layer membrane structure including an organic polymer layer, an ultra-thin graphyne transition layer grown on the surface of a porous base membrane, and a porous support layer.

[0031] In the graphyne multilayer composite mold, the graphyne transition layer and the organic polymer layer together constitute a selective separation layer.

[0032] The preparation method comprises the following steps:

[0033] Step 101, chemically modifying the surface of the porous base membrane with an amino-terminated silane coupling agent to make the surface of the base membrane have amino active groups, and then grafting small molecules with alkynyl groups that can react with amino groups to obtain a functional porous base membrane with an alkynyl-based group;

[0034] Step 102, dissolving a certain amount of graphyne monomer in a solvent, and adding a certain amount of copper acetate powder, stirring and ultrasonically treating, to prepare a graphyne monomer, copper acetate mixed solution; immersing the porous base film on which the acetylene layer is grown in step a in the monomer copper acetate solution, and reacting at a certain temperature for 2-6 hours, so that the graphene diyne material is fully grown on the surface of the porous base film.

[0035] Step 103, taking a certain amount of organic polymer, a crosslinking agent, and a catalyst in a certain proportion and mixing them evenly to form a crosslinking solution, then mixing the crosslinking solution and an organic solvent evenly to form a casting liquid 1, and immersing the porous base membrane loaded with graphyne in step 102 in the casting liquid 1, and the amount of the casting liquid added is 5-20L / m 2 After the organic solvent is evaporated for 3-12 hours, the film is placed in an environment of 80°C for reaction for 8 hours to obtain a Graphene acetylene multilayer composite mold.

[0036] Specifically, in step 101, chemical modification of the surface of the porous base membrane using an amino-terminated silane coupling agent means: immersing the porous base membrane in an ethanol solution of the amino-terminated silane coupling agent at a concentration of 0.1-1 mM, reacting at 100-150° C. for 1-3 hours under nitrogen protection; wherein the concentration of the amino-terminated silane coupling agent can be 0.1 mM, 0.3 mM, 0.5 mM, 0.7 mM, 1 mM, the reaction temperature can be 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., and the reaction time can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours; such a setting can ensure that the aminosilane coupling agent reacts fully with the base membrane, and a layer of amino groups is evenly grafted on the surface of the base membrane, which is conducive to the subsequent growth of the covalent organic skeleton separation layer.

[0037] Specifically, the terminal amino silane coupling agent includes γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethoxydimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethoxydiethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane, aminoethylaminoethylaminopropyltrimethoxysilane, and polyaminoalkyltrialkylsilane.

[0038] Specifically, grafting of alkynyl-containing small molecule organic matter in step 101 refers to: immersing the porous base membrane after surface amination in an ethanol solution containing alkynyl small molecules that react with amino groups at a concentration of 0.5-50 mg / ml, and reacting at 100-150°C for 1-3 hours; wherein the concentration of the alkynyl small molecule organic matter can be 0.5 mg / ml, 1.5 mg / ml, 2.5 mg / ml, 3.5 mg / ml, 5 mg / ml, the reaction temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, and the reaction time can be 1h, 1.5h, 2h, 2.5h, 3h; such an arrangement can make the alkynyl small molecule organic matter uniformly grafted to the surface of the base membrane, so that the subsequent graphene material can grow uniformly on the surface of the base membrane.

[0039] Preferably, the small molecule containing an alkynyl group that reacts with an amino group includes one or more of 4-ethynylbenzaldehyde, 3-ethynylbenzaldehyde, 2-ethynylbenzaldehyde, 5-ethynylisophthalic acid, 4-ethynylbenzoic acid, 3,5-diethynylbenzoic acid, 3-ethynylbenzoic acid, 2-ethynylbenzoic acid, 3-ethynyl-4-methylbenzoic acid, and 2-chloro-4-ethynylbenzoic acid.

[0040] Specifically, in the graphyne monomer solution described in step 102, the graphyne monomer is 1,3,5-triethynylbenzene; the concentration of the graphyne monomer is 0.4-5 mg / ml, and the specific concentration can be 0.4 mg / ml, 0.8 mg / ml, 1 mg / ml, 2 mg / ml, 3 mg / ml, etc., to ensure that the graphyne film grows fully on the surface of the base film to form a dense and defect-free selective separation layer; the solvent is selected from one of methanol, ethanol, and n-propanol; the concentration of cupric acetate is 0.2-1 g / L, and the specific concentration is 0.5 g / L, so that the graphyne monomer has a suitable reaction rate in the solvent.

[0041] The reaction temperature in step 102 is 100-150° C. for 2-6 hours.

[0042] Specifically, the organic polymer is one or more of polydimethylsiloxane (PDMS), polyether block polyamide (PEBA), polyphenylmethylsiloxane (PPMS), polytrifluoropropylmethylsiloxane (PTFMS) or polytrimethylsilyl propyne (PTMSP); the crosslinking agent is one or more of tetraethyl orthosilicate (TEOS), propoxypropyl orthosilicate (TPOS), vinyl triethoxysilane (VTES), ethyl triethoxysilane (ETES) or trifluoropropyl triethoxysilane (TFPTES); the catalyst is one or more of dibutyltin dilaurate (DBTDL), monobutyltin oxide (MBTO), dibutyltin oxide (DBTO), tripropyltin oxide (TPTO) or chloroplatinic acid.

[0043] Specifically, the thickness of the transition layer composed of in-situ grown graphyne is 100-400nm, the thickness of the organic polymer layer is 1-5μm, and the thickness of the selective separation layer composed of the transition layer composed of in-situ grown graphyne and the organic polymer layer is 1.1-5.4μm.

[0044] Preferably, the porous base membrane is an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane. The organic polymer membrane may be a polysulfone membrane (PSf), a polyethylene membrane (PE), a polyethersulfone membrane (PES), a polytetrafluoroethylene membrane (PTFE), a polyvinylidene fluoride membrane (PVDF), etc.; the inorganic membrane may be an aluminum oxide membrane (Al2O3), a zirconium oxide membrane (ZrO2), a zinc oxide membrane (ZnO), etc.; the organic / inorganic hybrid membrane may be a polysulfone / SiO2 membrane, a polysulfone / MOF membrane, a polysulfone / molecular sieve membrane, a polyvinylidene fluoride / SiO2 membrane, etc.; the average pore size of the porous base membrane is 10-100nm; the shape of the porous base membrane may be a flat plate, a tubular or a hollow fiber.

[0045] Preferably, the method for loading the organic polymer in step 103 is one or more of vacuum filtration, titration coating, spray coating, and dip coating.

[0046] Preferably, the organic solvent in step 103 may be one or more of ethanol, n-heptane, n-hexane or cyclohexane; the content of the cross-linking agent in the cross-linking solution may be 5wt.%, 10wt.%, 15wt.%, 20wt.%, 25wt.%, and the content of the catalyst may be 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%; and the content of the cross-linking solution in the casting solution may be 10wt.%, 15wt.%, 20wt.%, 25wt.%, 30wt.%.

[0047] The present invention will be further described below through specific examples.

[0048] In the following specific examples, the operations involved, if the conditions are not specified, are all carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials used, if the manufacturers and specifications are not specified, are all conventional products that can be obtained from the market.

[0049] Example 1

[0050] A tubular ceramic (Al2O3) porous base membrane was used, and the average pore size and porosity of the base membrane were 0.1 μm and 40% respectively; the terminal amino silane coupling agent γ-aminopropyl triethoxysilane was selected to chemically modify the base membrane. The organic polymer selected was polydimethylsiloxane (PDMS), the cross-linking agent selected was tetraethyl orthosilicate (TEOS), the catalyst selected was dibutyltin dilaurate (DBTDL), and the organic solvent selected was n-heptane.

[0051] Step a, immersing the tubular ceramic base membrane in an ethanol solution of an amino-terminated silane coupling agent with a concentration of 1 mM, reacting at 110° C. for 2 hours after nitrogen protection, so that the base membrane surface has amino active groups; then immersing the amination-treated porous base membrane in an ethanol solution of 4-ethynylbenzaldehyde with a concentration of 1 mg / ml, and reacting at 110° C. for 2 hours to obtain a porous base membrane with alkynyl growth;

[0052] Step b, dissolving 10 mg of triacetylene benzene and 15 mg of cupric acetate in 25 ml of ethanol, stirring and ultrasonically treating to prepare a monomer-catalyst mixed solution; vertically immersing the functionalized tubular ceramic base membrane in step a in the prepared monomer-catalyst solution, and reacting at 110° C. for 3 hours, and naturally cooling to room temperature to allow graphyne to fully grow on the surface of the porous base membrane.

[0053] Step c, taking polydimethylsiloxane (PDMS), 10wt.% of cross-linking agent tetraethyl orthosilicate (TEOS), and 1wt.% of catalyst dibutyltin dilaurate (DBTDL) and mixing them evenly to form a cross-linking solution, then mixing the 10wt.% cross-linking solution with n-heptane to form a casting liquid 1, immersing the porous base membrane on which graphyne is grown in step b in a certain amount of casting liquid 1, leaving a part of the casting liquid 1 on the surface of the graphyne transition layer to form a corresponding organic polymer layer; then after the organic solvent is volatilized for 3 hours, the membrane is placed in an environment of 80°C for reaction for 8 hours to obtain a graphyne multilayer composite mold.

[0054] Figure 1 Figure 1-1 shows that the water contact angle of the Graphene multilayer composite mold prepared in this example is 131°, which has good hydrophobicity. Figure 1 1-2) shows that the surface of the prepared Graphene multilayer composite film is uniform and has no defects, and the cross section ( Figure 1 Figure 1-3) shows that the prepared Graphene multilayer composite film has an organic polymer layer thickness of about 3.2 μm. Figure 1 Figure 1-4) shows that the thickness of the graphyne transition layer is about 150nm. Figure 1 1-5 shows that the water contact angle of the Graphene transition layer is 145°, showing strong hydrophobicity. The SEM surface ( Figure 1 1-6) show that the surface of the prepared graphyne transition layer is uniform.

[0055] The prepared Graphene multilayer composite module was placed in a pervaporation device for performance testing. The test conditions were as follows: (1) the raw material liquid composition was 5 wt.% ethanol aqueous solution, and the feed temperature was 60°C; (2) the membrane downstream pressure was 200 Pa.

[0056] The pervaporation performance of the Graphene multilayer composite module was measured as follows: the permeation flux was 3864 gm -2 h -1 , the separation factor is 10.51, and the ethanol content in the permeate is 36wt.%.

[0057] Comparative experiment 1

[0058] A tubular ceramic (Al2O3) porous base membrane was used, and the average pore size and porosity of the base membrane were 0.1 μm and 40% respectively; the terminal amino silane coupling agent γ-aminopropyl triethoxysilane was selected to chemically modify the base membrane. The organic polymer selected was polydimethylsiloxane (PDMS), the cross-linking agent selected was tetraethyl orthosilicate (TEOS), the catalyst selected was dibutyltin dilaurate (DBTDL), and the organic solvent selected was n-heptane.

[0059] Step a, take polydimethylsiloxane (PDMS), 10wt.% of cross-linking agent tetraethyl orthosilicate (TEOS), and 1wt.% of catalyst dibutyltin dilaurate (DBTDL) and mix them evenly to form a cross-linking solution, then mix the 10wt.% cross-linking solution with ethanol to form a casting liquid 2, immerse the ceramic tube in the casting liquid 2, and leave a part of the casting liquid 2 on the surface to form a corresponding organic polymer layer; then after the organic solvent is volatilized for 3 hours, the film is placed in an environment of 80°C for reaction for 8 hours to obtain a graphyne multilayer composite mold.

[0060] Figure 2 Figure 2-1 shows that the water contact angle of the pure PDMS membrane prepared in this example is 124°. SEM results ( Figure 2 Figure 2-2 shows that the surface of the prepared pure PDMS membrane is dense and has no defects. Figure 2 Figure 2-3 shows that the prepared pure PDMS membrane has a two-layer structure, in which the thickness of the organic polymer layer is 3.2 μm.

[0061] The prepared PDMS polymer membrane was placed in a pervaporation device for performance testing. The test conditions were: (1) the raw liquid composition was 5 wt.% ethanol aqueous solution, and the feed temperature was 60°C; (2) the membrane downstream pressure was 200 Pa.

[0062] The pervaporation performance of the Graphene multilayer composite module was measured as follows: the permeation flux was 4081 gm -2 h -1 , the separation factor is 6.983, and the ethanol content in the permeate is 27wt.%.

[0063] Comparative experiment 2

[0064] A tubular ceramic (Al2O3) porous base membrane was used, and the average pore size and porosity of the base membrane were 0.1 μm and 40% respectively; the terminal amino silane coupling agent γ-aminopropyl triethoxysilane was selected to chemically modify the base membrane. The organic polymer selected was polydimethylsiloxane (PDMS), the cross-linking agent selected was tetraethyl orthosilicate (TEOS), the catalyst selected was dibutyltin dilaurate (DBTDL), and the organic solvent selected was n-heptane.

[0065] Step a, take polydimethylsiloxane (PDMS), 10wt.% of cross-linking agent tetraethyl orthosilicate (TEOS), and 1wt.% of catalyst dibutyltin dilaurate (DBTDL) and mix them evenly to form a cross-linking solution, then mix 0.1wt.% of graphyne monomer, 10wt.% of cross-linking solution and ethanol evenly to prepare a casting liquid 3, immerse the ceramic tube in the casting liquid 3, and leave a part of the casting liquid 3 on the surface to form a corresponding organic polymer layer; then after the organic solvent is volatilized for 3 hours, the film is placed in an environment of 80°C for reaction for 8 hours to obtain a graphyne multilayer composite mold.

[0066] Figure 3 Figure 3-1 shows that the water contact angle of the Graphene mixed matrix membrane prepared in this example is 132°. SEM results ( Figure 3 3-2) shows that the surface of the prepared Graphene Oxygen Mixed Matrix Membrane is dense. Figure 3 Figure 3-3 shows that the prepared Graphene Oxygen Mixed Matrix Film has a two-layer structure, in which the thickness of the mixed matrix layer is 3.2 μm.

[0067] The prepared PDMS polymer membrane was placed in a pervaporation device for performance testing. The test conditions were: (1) the raw liquid composition was 5 wt.% ethanol aqueous solution, and the feed temperature was 60°C; (2) the membrane downstream pressure was 200 Pa.

[0068] The pervaporation performance of the Graphene multilayer composite module was measured as follows: the permeation flux was 3309 gm -2 h -1 , the separation factor is 6.653, and the ethanol content in the permeate is 26wt.%.

[0069] Example 2

[0070] A tubular ceramic (Al2O3) porous base membrane was used, and the average pore size and porosity of the base membrane were 0.1 μm and 40% respectively; the terminal amino silane coupling agent γ-aminopropyl triethoxysilane was selected to chemically modify the base membrane. The organic polymer selected was polydimethylsiloxane (PDMS), the cross-linking agent selected was tetraethyl orthosilicate (TEOS), the catalyst selected was dibutyltin dilaurate (DBTDL), and the organic solvent selected was n-heptane.

[0071] Step a, immersing the tubular ceramic base membrane in an ethanol solution of an amino-terminated silane coupling agent with a concentration of 1 mM, reacting at 110° C. for 2 hours after nitrogen protection, so that the base membrane surface has amino active groups; then immersing the amination-treated porous base membrane in an ethanol solution of 4-ethynylbenzaldehyde with a concentration of 1 mg / ml, and reacting at 110° C. for 2 hours to obtain a porous base membrane with alkynyl growth;

[0072] Step b, dissolving 20 mg of triacetylene benzene and 15 mg of cupric acetate in 25 ml of ethanol, stirring and ultrasonically treating to prepare a monomer-catalyst mixed solution; vertically immersing the functionalized tubular ceramic base membrane in step a in the prepared monomer-catalyst solution, and reacting at 110° C. for 3 hours, and naturally cooling to room temperature to allow graphyne to fully grow on the surface of the porous base membrane.

[0073] Step c, taking polydimethylsiloxane (PDMS), 10wt.% of cross-linking agent tetraethyl orthosilicate (TEOS), and 1wt.% of catalyst dibutyltin dilaurate (DBTDL) and mixing them evenly to form a cross-linking solution, then mixing the 10wt.% cross-linking solution with n-heptane to form a casting liquid 1, and immersing the porous base membrane on which graphyne is grown in step b in a certain amount of casting liquid 1. Due to the porous structure of the grown graphyne transition layer, the casting liquid 1 will partially penetrate into the graphyne transition layer, and a part of the casting liquid 1 will remain on the surface of the graphyne transition layer to form a corresponding organic polymer layer; then, after the organic solvent is volatilized for 3 hours, the membrane is placed in an environment of 80°C for reaction for 8 hours to obtain a graphyne multilayer composite mold.

[0074] The prepared Graphene multilayer composite module was placed in a pervaporation device for performance testing. The test conditions were as follows: (1) the raw material liquid composition was 5 wt.% ethanol aqueous solution, and the feed temperature was 60°C; (2) the membrane downstream pressure was 200 Pa.

[0075] The pervaporation performance of the Graphene multilayer composite module was measured as follows: the permeation flux was 2847 gm -2 h -1 , the separation factor is 8.33, and the ethanol content in the permeate is 31wt.%.

[0076] Example 3

[0077] A tubular ceramic (Al2O3) porous base membrane was used, and the average pore size and porosity of the base membrane were 0.1 μm and 40% respectively; the terminal amino silane coupling agent γ-aminopropyl triethoxysilane was selected to chemically modify the base membrane. The organic polymer selected was polydimethylsiloxane (PDMS), the cross-linking agent selected was tetraethyl orthosilicate (TEOS), the catalyst selected was dibutyltin dilaurate (DBTDL), and the organic solvent selected was n-heptane.

[0078] Step a, immersing the tubular ceramic base membrane in a toluene solution of an amino-terminated silane coupling agent with a concentration of 1 mM, reacting at 110° C. for 2 hours after nitrogen protection, so that the base membrane surface has amino active groups; then immersing the amination-treated porous base membrane in a toluene solution of 4-ethynylbenzaldehyde with a concentration of 1 mg / ml, and reacting at 110° C. for 2 hours to obtain a porous base membrane with alkynyl growth;

[0079] Step b, dissolving 10 mg of triacetylene benzene and 15 mg of cupric acetate in 25 ml of ethanol, stirring and ultrasonically treating to prepare a monomer-catalyst mixed solution; vertically immersing the functionalized tubular ceramic base membrane in step a in the prepared monomer-catalyst solution, and reacting at 110° C. for 3 hours, and naturally cooling to room temperature to allow graphyne to fully grow on the surface of the porous base membrane.

[0080] Step c, taking polydimethylsiloxane (PDMS), 10wt.% of cross-linking agent tetraethyl orthosilicate (TEOS), and 1wt.% of catalyst dibutyltin dilaurate (DBTDL) and mixing them evenly to form a cross-linking solution, then mixing the 10wt.% cross-linking solution with n-heptane to form a casting liquid 1, and immersing the porous base membrane on which graphyne is grown in step b in a certain amount of casting liquid 1. Due to the porous structure of the grown graphyne transition layer, the casting liquid 1 will partially penetrate into the graphyne transition layer, and a part of the casting liquid 1 will remain on the surface of the graphyne transition layer to form a corresponding organic polymer layer; then, after the organic solvent is volatilized for 3 hours, the membrane is placed in an environment of 80°C for reaction for 8 hours to obtain a graphyne multilayer composite mold.

[0081] The prepared Graphene multilayer composite module was placed in a pervaporation device for performance testing. The test conditions were as follows: (1) the raw material liquid composition was 5 wt.% ethanol aqueous solution, and the feed temperature was 60°C; (2) the membrane downstream pressure was 200 Pa.

[0082] The pervaporation performance of the Graphene multilayer composite module was measured as follows: the permeation flux was 3360 gm -2 h -1 , the separation factor is 9.18, and the ethanol content in the permeate is 33wt.%.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A Graphene Multilayer Composite Mould, characterized in that: It is divided into three layers, from top to bottom: an organic polymer layer, a graphyne transition layer, and a lower porous base membrane support layer; the graphyne transition layer is on the upper surface of the porous base membrane, and grows upward from the upper surface of the porous base membrane; the organic polymer layer is loaded on the surface of the graphyne transition layer; the graphyne transition layer and the organic polymer layer together constitute a selective separation layer.

2. A Graphene Oxide Multilayer Composite Mold according to claim 1, characterized in that: The thickness of the ultra-thin graphyne transition layer composed of in-situ grown graphyne is 100-400nm, and the thickness of the organic polymer layer is 1-5μm; the thickness of the selective separation layer composed of the ultra-thin graphyne transition layer and the organic polymer layer is 1.1-5.4μm.

3. A Graphene Oxide Multilayer Composite Mold according to claim 1, characterized in that: The graphyne monomer used in growing the graphyne transition layer is 1,3,5-triethynylbenzene.

4. A Graphene Oxide Multilayer Composite Mold according to claim 1, characterized in that: The porous base membrane is an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane, and the average pore size is 10-100nm; the shape of the porous base membrane is a flat plate, a tube or a hollow fiber.

5. A Graphene Oxide Multilayer Composite Mold according to claim 1, characterized in that: The organic polymer is one or more of polydimethylsiloxane (PDMS), polyether block polyamide (PEBA), polyphenylmethylsiloxane (PPMS), polytrifluoropropylmethylsiloxane (PTFMS) or polytrimethylsilyl propyne (PTMSP).

6. The method for preparing a Graphene Oxide Multilayer Composite Mould according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step a, chemically modifying the surface of the porous base film with an amino-terminated silane coupling agent to make the surface of the base film have amino active groups, and then grafting small molecules with alkynyl groups that can react with amino groups to obtain a functional porous base film with an alkynyl-based layer; Step b, dissolving a certain amount of graphyne monomer in a solvent, adding copper acetate powder, stirring and ultrasonically treating, to prepare a mixed solution of graphyne monomer and copper acetate; immersing the functionalized porous base film on which the acetylene base layer is grown in step a in the mixed solution, and reacting at a certain temperature, so that the graphyne transition layer is fully grown on the surface of the porous base film; Step c, taking an organic polymer, a cross-linking agent, and a catalyst and mixing them evenly to form a cross-linking solution, then mixing the cross-linking solution and an organic solvent evenly to form a casting liquid 1, adding a certain amount of the casting liquid 1 to the surface of the porous base film on which the graphyne transition layer is grown in step b, leaving a portion of the casting liquid 1 on the surface of the graphyne transition layer to form a corresponding organic polymer layer; then after the organic solvent is volatilized for 3-12 hours, the membrane is placed in an environment of 80°C to react for 8 hours to obtain a graphyne multilayer composite membrane.

7. The method according to claim 6, characterized in that The method of chemically modifying the surface of the porous base film by using an amino-terminated silane coupling agent in step a is preferably as follows: the porous base film is immersed in an ethanol solution of an amino-terminated silane coupling agent with a concentration of 0.1-1 mM, and reacted at 100-150° C. for 1-3 hours after nitrogen protection; the amino-terminated silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethoxydimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethoxydiethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane, aminoethylaminoethylaminopropyltrimethoxysilane, and polyaminoalkyltrialkylsilane; The small molecule with alkynyl group that is grafted and reacts with amino group in step a is one or more of 4-ethynylbenzaldehyde, 3-ethynylbenzaldehyde, 2-ethynylbenzaldehyde, 5-ethynylisophthalic acid, 4-ethynylbenzoic acid, 3,5-diethynylbenzoic acid, 3-ethynylbenzoic acid, 2-ethynylbenzoic acid, 3-ethynyl-4-methylbenzoic acid, and 2-chloro-4-ethynylbenzoic acid. The porous base film after surface amination is immersed in an ethanol solution of the small molecule with alkynyl group that reacts with amino group at a concentration of 0.5-5mg / ml, and reacted at 100-150°C for 1-3h; Step b, the graphyne monomer is 1,3,5-triethynylbenzene; the concentration of the graphyne monomer is 0.4-5 mg / ml; the solvent used is selected from one of methanol, ethanol and n-propanol; the concentration of copper acetate is 0.2-1 g / L, and the reaction at a certain temperature refers to the reaction at 100°C-150°C for 2-6 hours; The organic polymers described in step c are one or more of polydimethylsiloxane (PDMS), polyether block polyamide (PEBA), polyphenylmethylsiloxane (PPMS), polytrifluoropropylmethylsiloxane (PTFMS) or polytrimethylsilyl propyne (PTMSP); The crosslinking agent is one or more of tetraethyl orthosilicate (TEOS), propyl orthosilicate (TPOS), vinyl triethoxysilane (VTES), ethyl triethoxysilane (ETES) or trifluoropropyl triethoxysilane (TFPTES); the catalyst is one or more of dibutyltin dilaurate (DBTDL), monobutyltin oxide (MBTO), dibutyltin oxide (DBTO), tripropyltin oxide (TPTO) or chloroplatinic acid.

8. The method according to claim 6, characterized in that The content of the organic polymer in the casting solution 1 in step c is 5wt.%-50wt.%; The organic solvent in step c is one or more of ethanol, n-heptane, n-hexane or cyclohexane; the content of the crosslinking agent in the crosslinking solution is 1wt.%-30wt.%, and the content of the catalyst is 0.1wt.%-5wt.%; The method for loading the organic polymer in step c is one or more of vacuum filtration, titration coating, spray coating, and dip coating.

9. Use of the Graphene Oxygen Multilayer Composite Membrane according to any one of claims 1 to 5 to separate bio-alcohol from aqueous solution or fermentation broth by pervaporation.

Citation Information

Patent Citations

  • Preparation method of graphdiyne oxide membrane material for adsorbing and separating uranium

    CN114572960A

  • Method for in-situ preparation of graphdiyne separation membrane

    CN114917773A

  • Ultrafast preparation method of graphdiyne composite membrane

    CN115869785A

  • Graphite alkynyl alcohol permselective pervaporation membrane and preparation method thereof

    CN117582822A

  • Solar seawater desalination membrane, preparation method thereof and seawater desalination treatment method

    CN118122154A

Cited By

  • Graphite diacetylene phase change composite material and preparation method thereof

    CN117384386A

  • Graphdiyne phase change composite material and preparation method thereof

    CN117384386B

  • Graphite alkynyl alcohol permselective pervaporation membrane and preparation method thereof

    CN117582822A

  • Graphyne-based preferential alcohol permeation pervaporation membrane and preparation method thereof

    CN117582822B

  • Method for preparing b-axis orientation MFI type molecular sieve separation membrane through in-situ crystallization

    CN120420832A